Evaluating Customer Satisfaction with Mobile Banking Services: A User-Centric Study - Dongol, Padam; Paudel, Pratiksha (MVIC Journal of Management and Information Technology, 2025)
The rapid growth of smartphones and wider internet access has boosted mobile banking usage across various user groups. Yet, it is still unclear which service features customers value most and how these shape their satisfaction. This study examines the determinants of customer satisfaction with mobile banking in Kathmandu Valley, Nepal. As mobile banking becomes central to digital finance, identifying the drivers of satisfaction is crucial for banks aiming to improve services and retain users. The research emphasizes six independent variables—Usefulness of Mobile Banking (UOM), Ease of Use (EOU), Cost of Use (COU), Trust on Mobile Banking (TOM), Security Factor (SF), and Time Factor (TF)—and their relationship with the dependent variable, Customer Satisfaction (CS). Data were collected from 205 mobile banking users through a structured questionnaire covering demographics and perceptions, measured on a 5-point Likert scale. Using SPSS, the study applied descriptive statistics, correlation, and multiple regression analysis. Findings revealed that trust, security, cost, and time factors significantly affect satisfaction, whereas usefulness and ease of use, though positively correlated, did not emerge as significant predictors in the regression model.